Dead man's folly - Christie, Agatha, 1890-1976. (New York : Berkley Books, 2000)
Hercule Poirot is summoned by his old acquaintance, writer-detective Ariadne Oliver, to attend a "Murder Hunt" at Nasse House in Devonshire.
5.0.
5.0
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction; England -- Fiction; England -- Fiction